Review and selection of optimal sensors for building a production facility microclimate monitoring system - Fesenko, A.; Sotnik, S. (ХНУРЕ, 2025)
The study examines modern sensors for monitoring the microclimate of industrial premises, such as temperature, humidity, pressure, CO₂ concentration, dust, noise, and light sensors. A review of their characteristics and selection criteria, such as accuracy, cost, reliability, power consumption, and ease of integration, was conducted. The selection of specific sensors for the indoor (BME280 + MH Z19D) and outdoor (BMP290L + SHT40) modules is justified. The obtained results demonstrate an optimal balance between functionality, accuracy, and cost effectiveness for building a microclimate monitoring system. Дослідження розглядає сучасні сенсори для моніторингу мікроклімату приміщень промислового призначення, такі як сенсори температури, вологості, тиску, концентрації CO₂, пилу, шуму та освітленості. Було проведено огляд їх характеристик та критеріїв вибору, таких як точність, вартість, надійність, споживання енергії та простота інтеграції. Обґрунтовано вибір конкретних сенсорів для внутрішнього (BME280 + MH Z19D) та зовнішнього (BMP290L + SHT40) модулів. Отримані результати демонструють оптимальний баланс між функціональністю, точністю та економічною ефективністю для системи моніторингу мікроклімату в будівлі.
Keywords: microclimate monitoring; sensors; temperature; моніторинг мікроклімату